The Perception of Travel Behavior on Public Transport Mode Choice: A Case of Depok-Jakarta Route - Rahmadhani, Ajeng Widyaningrum; Rifai, Andri Irfan; Handayani, Susanty (DAS Institute, 2022)
Traffic congestion is a major unresolved problem and a joint task of the community and the government. A high level of mobility will be directly proportional to traffic congestion, and public transportation is an efficient solution for dealing with this problem. This research aims to determine the public's perception of choosing public transportation along the Depok-Jakarta route. The data collection method will be carried out by distributing questionnaires online through social media. Respondent data processing is presented using a spider chart in Microsoft Excel. The results indicate that most public transportation users are millennials and women. This generation prefers the Commuter Line (KRL) compared to other transportation. Schedule accuracy, level of comfort and security, disability friendliness, adequate facilities, infrastructure, and affordable costs are considerations in choosing public transportation. The KRL is highly interested in using it and has a positive service perception.